Microbiological and physicochemical assessment of artisanally produced “Alheira” fermented sausages in Northern Portugal - Coelho-Fernandes, Sara (2022)
Alheira is a traditional non-ready-to-eat sausage produced mainly in northern Portugal. The objective of this study was to evaluate the associations between some relevant physicochemical and microbiological attributes of alheiras produced by different regional producers. Finished products from 8 regional factories amounting to 40 samples were analyzed. Counts of mesophiles, lactic acid bacteria, Staphylococcus aureus, presumptive Clostridium perfringens, and Salmonella spp., as well as pH, water activity (aW), and proximate analysis were determined. Principal component analysis (PCA) of these variables was conducted to construct quality maps. Three meaningful components were extracted, accounting for 63% of data variability. PC1 (26% data variability) was positively associated with LAB, mesophiles, and S. aureus, characterizing therefore longer fer- mentation. PC2 (22% data variability) correlated negatively with moisture, aW and positively with C. perfringens, and thus has been linked to greater dehydration of sausages. PC3 (15% data varia- bility) correlated positively with pH and protein content, implying the use of more meat in the formulation. This preliminary work has identified three quality factors underpinning the variabil- ity in artisanal alheiras; and has also highlighted the need to implement better microbiological control and process standardization during the production of artisanal alheiras.